The role of shame, self-criticism and self-compassion in persistent, treatment resistant depression - Garland, Anne (2022)
Background In 2017 the World Health Organisation (WHO), declared depression to be the leading cause of disability adjusted life years lost due to ill-health. Further, it is well established in the research literature that depression is a relapsing illness. In using Cognitive -Behavioural Therapy (CBT) with patients diagnosed with persistent, treatment resistant depression two clinical observations underpin this thesis. Firstly, that shame and self-criticism are key features of depression and secondly that standard Beckian CBT interventions have limited impact in tackling shame and self-criticism in this patient group. Integrating Compassion Focused Therapy (CFT) with CBT interventions results in some amelioration of shame and self-criticism, but this is limited empirically.